2019
DOI: 10.1029/2018ja026316
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Geomagnetic Storm of 7‐8 September 2017 on the Swarm Precise Orbit Determination

Abstract: We analyze a recent geomagnetic storm event on 7‐8 September 2017 to investigate the impact of geomagnetic storm on the precise orbit determination (POD) of Swarm constellation. The storm time performance of POD is analyzed. The quality of Swarm orbits are severely degraded during the storm main phase on 8 September and the maximum precision degradation reached over 10 cm. The enhanced thermospheric mass density at Swarm altitude during the storm enlarges the atmosphere drag for low Earth orbit satellites, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Savitzky‐Golay filter fitted the background with a linear basis function set based on least squares in a series of frames of a given length determined by the cut off period. This method has been widely used in processing dTEC data to show TID, and could extract the wave structure effectively (K. Zhang et al., 2019; S. R. Zhang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Savitzky‐Golay filter fitted the background with a linear basis function set based on least squares in a series of frames of a given length determined by the cut off period. This method has been widely used in processing dTEC data to show TID, and could extract the wave structure effectively (K. Zhang et al., 2019; S. R. Zhang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A geomagnetic storm, which was triggered by a coronal mass ejection that broke out on 7-8 September 2017, was analyzed to investigate the impact of spaceborne observational errors on the BDS POD [35]. Studies show that the quality of the LEO constellations, i.e., the Swarm constellation, are severally degraded during the main phases of storms and that the maximum degradation of the orbit accuracy can be over 10 cm [18]. The main reason for the Swarm orbit accuracy degradation is the enhanced thermospheric mass density at the Swarm altitude, which increased the atmospheric drag for the LEO satellites.…”
Section: Gnss/leo Combined Pod During a Solar Stormmentioning
confidence: 99%
“…Degraded GNSS signals can reduce the availability and reliability of the GNSS-based POD. In addition, with increasing ionospheric density, the accuracy of a conventional orbit determination is seriously reduced [18].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the high-order ionospheric (HOI) terms are neglected since it was reported that they were not the main cause of LEO satellite systematic errors near the magnetic equatorial area. In addition, the orbit accuracy improvement with HOI terms corrected could be very limited [35][36][37]. The IF observation equations are formulated as follows:…”
Section: Observation Modementioning
confidence: 99%